Improve Wettability of Polycaprolactone (PCL) /Chitosan of Wound Dressings by Plasma Jet - Mohsen, Ali H.; Ali, Nadia A. (Iraqi Journal of Science, 2022)
Surface wettability plays a significant role in determining the function of the wound dressing. They should have hydrophobic surfaces for the adsorption of bacteria and a hydrophilic surface necessary to improve cell attachment for most anchorage-dependent cell types. Furthermore, the Hydrophobicity / Hydrophilicity of the surface can be used to direct cellular processes such as cell initial correlation, adhesion, and migration during wound healing, as a result such surface can change its surface wettability which increases the dressing’s usefulness. In this research, nanomembres were prepared from polycaprolactone and chitosan solution (with different amounts of CS (0.05, 0.1, 0.2, and 0.4) % (w/w)) by the electrospinning method. These membranes were characterized by Fourier-transform infrared FTIR spectroscopy and their wettability, contact angle, porosity and swelling values were determined. These were improved by plasma treating the electrospun nanomebranes. Best results were obtained for the plasma treated electrospum nanomembranes at 4% chitosan. It resulted in a surface with a combination of hydrophobic and hydrophilic patterns, which has a lot of promise in the realm of tissue engineering for things like cell patterning and guiding.